Design, Synthesis, and Evaluation of Novel NSAIDs (Piroxicam Analogues) with Reduced Gastrointestinal Toxicity for Long-Term Management of Osteoarthritis - Dey, Tathagata; Kini, Deepthi D; Thenmozhi, V. (Journal of Neonatal Surgery, 2025)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs), including piroxicam, are widely used for long-term osteoarthritis management. However, their clinical utility is often limited by gastrointestinal (GI) toxicity, necessitating the development of safer alternatives. This study aimed to design, synthesize, and evaluate novel piroxicam analogues with improved anti-inflammatory and analgesic efficacy while minimizing GI side effects. Methods: Three novel piroxicam analogues—4-hydroxy-2-methyl-N-phenyl-2H-thieno[2,3-e][1,2]thiazine-3-carboxamide 1,1-dioxide (PA-1), 4-hydroxy-2-ethyl-N-(4-methoxyphenyl)-2H-thieno[2,3-e][1,2]thiazine-3-carboxamide 1,1-dioxide (PA-2), and 4-hydroxy-2-propyl-N-(3-chlorophenyl)-2H-thieno[2,3-e][1,2]thiazine-3-carboxamide 1,1-dioxide (PA-3)—were synthesized through rational structural modifications aimed at enhancing COX-2 selectivity. Structural characterization was performed using FTIR, NMR, MS, and elemental analysis. The pharmacological evaluation included COX inhibition assays, an anti-inflammatory carrageenan-induced paw edema model, and an analgesic acetic acid-induced writhing test. Gastrointestinal toxicity was assessed using an ethanol-induced gastric ulcer model. Pharmacokinetic properties were determined through bioavailability and plasma half-life studies. Results: The synthesized analogues demonstrated superior COX-2 selectivity, with PA-1 exhibiting the highest inhibition (IC₅₀: 0.72 µM for COX-2 vs. 3.8 µM for COX-1). In vivo, PA-1 showed the most potent anti-inflammatory activity (52.6 ± 2.3% edema reduction) and highest analgesic effect (68.1 ± 2.6% writhing inhibition), outperforming piroxicam (48.3 ± 2.0% and 63.2 ± 2.5%, respectively). Notably, all analogues exhibited significantly lower ulcer indices compared to piroxicam (3.2 ± 0.5 for PA-1 vs. 12.4 ± 1.1 for piroxicam, p < 0.01). Pharmacokinetic analysis revealed enhanced bioavailability (PA-1: 89.2%) and prolonged plasma half-life (PA-1: 5.6 h) compared to piroxicam (76.5% and 4.3 h, respectively). Conclusion: The novel piroxicam analogues PA-1, PA-2, and PA-3 demonstrated enhanced anti-inflammatory and analgesic efficacy, reduced gastrointestinal toxicity, and improved pharmacokinetics compared to standard piroxicam. These findings suggest that these next-generation NSAIDs could serve as promising candidates for long-term osteoarthritis management with enhanced safety profiles. Further preclinical and clinical studies are warranted to confirm their therapeutic potential.